A review of recent advances in the science and technology of seawater-mixed concrete. (February 2022) - Ebead, Usama; Lau, Denvid; Lollini, Federica; Nanni, Antonio; Suraneni, Prannoy; Yu, Tao
Abstract: A review of the last 16 years of research (2005–2021) on seawater-mixed concrete is presented. A very significant amount of research, both fundamental and applied, has been performed on this topic, and there is worldwide interest in the use of seawater-mixed concrete to reduce concrete freshwater consumption. Seawater-mixed concrete should be used either for unreinforced concrete or for concrete using non-corrosive reinforcement (fiber reinforced polymer or stainless steel). The complex effects of seawater on hydration processes, concrete microstructure, and interactions with supplementary cementitious materials are relatively well understood. On the other hand, only limited information is available on the long-term durability of seawater-mixed concrete. Modeling of seawater-mixed concrete at a variety of scales appears to be nascent. A primary challenge with the large-scale adoption of seawater-mixed concrete remains the absence of codes and specifications that address the use of such material. As an increasing number of structures are constructed using seawater-mixed concrete and a greater understanding of long-term behavior is obtained, it is hoped that greater adoption for the right applications will eventually follow.